Home nutrition therapy: a review (Research, Society and Development, 2022)
Home nutritional therapy (HNT) can be defined as an effective care method, used for the recovery of the nutritional support of unhealthy individuals, and also as a nutritional and clinical subsidy for such patients, who are in their own homes or in hospitals. rest institutions. For the beginning of HNT, the performance of a qualified nutritionist who understands the patient's needs is essential. Therefore, the objective of the present review was to discuss the scientific evidence regarding home nutritional therapy. The research was carried out involving publications on oral/enteral/parenteral nutrition, home nutritional therapy, assistance from health agencies, and reduction of hospital beds on the platforms, PubMed (US National Library of Medicine), Scientific Electronic Library Online Brazil (SciELO), Web of Science and Portal Periodicos Capes of the last 15 years. The results show that HNT reduces complications and mortality, in addition to providing the patient with greater comfort and the opportunity to recover in their family environment.